Essential Judaism : a complete guide to beliefs, customs, and rituals - Robinson, George, 1953- (New York : Atria paperback, 2016)
This book is a comprehensive, hands-on volume that provides an up-to-date overview of the practices and beliefs of the Jews, as well as a guide to religious traditions, everyday practices, philosophical beliefs, and historical foundations of judaism.
Includes bibliographical references (pages 625-645) and index.
Keywords: Judaism; RELIGION -- Judaism -- History; RELIGION -- Judaism -- Rituals & Practice; Judaism